2011
DOI: 10.1021/ja203286n
|View full text |Cite
|
Sign up to set email alerts
|

Functional Virus-Based Polymer–Protein Nanoparticles by Atom Transfer Radical Polymerization

Abstract: Viruses and virus-like particles (VLPs) are useful tools in biomedical research. Their defined structural attributes make them attractive platforms for engineered interactions over large molecular surface areas. In this report, we describe the use of VLPs as multivalent macroinitiators for atom transfer radical polymerization (ATRP). The introduction of chemically reactive monomers during polymerization provides a robust platform for post-synthetic modification via the copper-catalyzed azide-alkyne cycloadditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
175
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 44 publications
1
175
0
Order By: Relevance
“…It was found that the overall structure was maintained even until 100 °C. Using the same approach for surface functionalization only with a radical initiator attached to the azide instead of a linear polymer, various polymers were grown from the surface via ATRP as described above [74]. The interesting thing is that there are several aspects, which can be combined in a viral-polymer system.…”
Section: Virus-polymer Conjugatesmentioning
confidence: 99%
“…It was found that the overall structure was maintained even until 100 °C. Using the same approach for surface functionalization only with a radical initiator attached to the azide instead of a linear polymer, various polymers were grown from the surface via ATRP as described above [74]. The interesting thing is that there are several aspects, which can be combined in a viral-polymer system.…”
Section: Virus-polymer Conjugatesmentioning
confidence: 99%
“…Among these technologies, platforms based on polymeric materials, especially biodegradable nanoparticles, are of particular interest due to the flexibility offered by macromolecular synthesis methods, high drug loading capacities, improved drug solubility, and their ease of multifunctionalization. [23][24][25] In this review, the developments in fluorescence imaging with the three polymer based platforms: cross-linked micelles, polymersomes and polymercore nanoparticles (cf. Figure 2), when coupled with the commonly used fluorophores, will be explored.…”
Section: Introductionmentioning
confidence: 99%
“…3,24−29 The versatility of RDRP techniques has also been further demonstrated in a rapidly growing area of bioconjugations using a "grafting-from" strategy, which uses a protein as a macroinitiator or macrochain transfer agent to grow polymers directly from the protein. 2,7,14,30,31,32 The grafting-from method provides some advantages compared to the grafting-to method such as purification (e.g., separation of unreacted monomers vs separation of unreacted polymers) and control over the number of polymers per protein.…”
Section: ■ Introductionmentioning
confidence: 99%